New Insights into Artesunate as a Pleiotropic Regulator of Innate and Adaptive Immune Cells - Lixian Lin; Zengqi Tang; Zhenrui Shi; Qing Guo; Hui Xiong (Journal of Immunology Research)
Artesunate, one of the derivatives of artemisinin (“qinghaosu” in Chinese), is known as an antimalarial drug with high efficiency and low toxicity. Of interest, emerging evidences suggest that artesunate also possesses an immunomodulatory effect during innate and adaptive immune responses in cell types and context-dependent manner. Although it shows promising application in many diseases, such as inflammatory diseases, hypersensitivity, autoimmune diseases, and cancers, little is known about underlying molecular. In this review, we summarize recent advances of how artesunate regulates innate and adaptive immune cells. In addition, its potential application in immune-related diseases is also highlighted.